Multilingualism in performance appraisal interviews: strategies to bridge language gaps - De Malsche, Fien; Tobback, Els; Vandenbroucke, Mieke (Frontiers in Communication, 2024)
This paper explores three multilingual strategies to bridge the lack of a shared first language as they are used during performance appraisal interviews, namely English as a business lingua franca, receptive multilingualism, and a lay interpreter. The study is based on authentic video-recorded performance appraisal interviews at a globally active Belgian company, and follow-up interviews with the managers. The analysis focuses on how the company deals with multilingualism from a management perspective, how the managers perceive these multilingual strategies from a language ideological perspective, and how these language ideological beliefs shape the language practices of the performance appraisal interviews. We conclude that this study provides novel insights into how globalized companies deal with multilingualism in the high-stakes and potentially sensitive interactional context of a performance appraisal interview by underlining the intertwined nature of language ideological beliefs and language practices as part of a broader multilingual language management strategy.